2010
DOI: 10.4161/psb.5.8.12338
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the one-MegaDalton JAZ1 protein complex

Abstract: JA-Ile, the endogenous bioactive JA, is perceived by the F-box protein CORONATINE INSENSITIVE1 (COI1) that functions as the hormone receptor. In the presence of JA-Ile, the E3 ubiquitin ligase complex SCF COI1 recognizes its targets, the JAZ proteins that are subsequently ubiquitinylated and destroyed by the 26S proteasome. [1][2][3][4][5] In an unelicited state, the JAZ proteins bind and inactivate the transcription factor MYC2, thereby repressing the activation of early JA-responsive genes through a mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Dimerization and higher-order multimerization of MYC (39, 95), JAZ (25, 29), and TPL (80) family members are consistent with the view that transcriptional repression of jasmonateresponsive genes involves large multiprotein complexes (46). There is evidence to indicate that these complexes exert epigenetic effects by navigating transcriptional constraints imposed by chromatin (4,38,97).…”
Section: Mediator Complex Subunit 25 (Med25)supporting
confidence: 66%
“…Dimerization and higher-order multimerization of MYC (39, 95), JAZ (25, 29), and TPL (80) family members are consistent with the view that transcriptional repression of jasmonateresponsive genes involves large multiprotein complexes (46). There is evidence to indicate that these complexes exert epigenetic effects by navigating transcriptional constraints imposed by chromatin (4,38,97).…”
Section: Mediator Complex Subunit 25 (Med25)supporting
confidence: 66%
“…The results showed that the CsJAZ family was mainly regulated by numerous transcription factor families, including ERF, MYB, bHLH, NAC, and TCP. Among them, the ERF members were most abundant (42), followed by the MYB (36) and NAC members (18). In additon, numerous TFs related to plant hormones were identified in this study, including ERF, CRF, and ARF TFs.…”
Section: Identification and Annotation Of The Csjaz Gene Putative Tramentioning
confidence: 54%
“…Thus, jasmonate signaling might be involved in the responses of Citrus roots to Mg-deficiency. However, the expression of the gene encoding ZIM/tify-domain (JAZ/TIFY), which is the co-repressor of MYC2 that is ubiquitinilated upon activation of jasmonate signaling cascade [ 78 ], did not change in Mg-deficient citrus roots (Additional file 2 ).…”
Section: Discussionmentioning
confidence: 99%